1999
DOI: 10.1042/bj3400017
|View full text |Cite
|
Sign up to set email alerts
|

Efficient transcription of the human angiotensin II type 2 receptor gene requires intronic sequence elements

Abstract: To investigate mechanisms of human angiotensin II type 2 receptor (hAT2) gene regulation we functionally characterized the promoter and downstream regions of the gene. 5'-Terminal deletion mutants from -1417/+100 to -46/+100 elicited significant but low functional activity in luciferase reporter gene assays with PC12W cells. Inclusion into the promoter constructs of intron 1 and the transcribed region of the hAT2 gene up to the translation start enhanced luciferase activity 6.7+/-1.6-fold and 11.6+/-1.7-fold (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…Our experiments, consistent with a previous publication [33], also demonstrated the important regulatory function of the exon 1-intron 1 region of the AT2R gene is necessary and sufficient for AT2R promoter activity, whereas upstream promoter elements (> 316 bp relative to exon 2) do not contribute to promoter activity to a major degree (Fig. 2&3).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our experiments, consistent with a previous publication [33], also demonstrated the important regulatory function of the exon 1-intron 1 region of the AT2R gene is necessary and sufficient for AT2R promoter activity, whereas upstream promoter elements (> 316 bp relative to exon 2) do not contribute to promoter activity to a major degree (Fig. 2&3).…”
Section: Discussionsupporting
confidence: 81%
“…In this context, our result of a single transcriptional start site within the TATA box positive AT2R promoter is consistent with the promoter architecture of a tissue-specific gene [36] in contrast to strong housekeeping genes associated with multiple start sites and the absence of a TATA motif [29,35]. It is noteworthy that two transcriptional start sites upstream the TATA box were identified in human uterus RNA by primer extension analysis [33] (Fig. 1A) which might reflect tissue specific differences and could affect mRNA stability.…”
Section: Discussionsupporting
confidence: 58%
“…The AT2-R gene has three exons, with the entire coding region on the third exon (13). Regulatory elements are located in the first intron in addition to the promoter region (14). The complete nucleotide sequence of the human AT2-R gene including the promoter region has been elucidated (13) and is publicly available via the World Wide Web in the NCBI sequence database (http://www.ncbi.nlm.nih.gov/) (12).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] In this study, reduced levels of FXIIIA antigen and mRNA were observed in the patients (Supplementary Table 3 and Supplementary Figure 5), suggesting that the Int1(+12)C4A mutation affects the expression of the F13A1 gene. To determine the functional effects of the Int1(+12)C4A mutation in the F13A1 gene, luciferase reporters were transiently expressed in U937 cells.…”
Section: Resultsmentioning
confidence: 99%